Best-loved stories told at the National Storytelling Festival - National Association for the Preservation and Perpetuation of Storytelling (U.S.) (Jonesborough, Tenn. : National Storytelling Press ; Little Rock, Ark. : Distributed to the book trade by August House Publishers, 1991)
A collection of thirty-seven traditional and adapted folk and fairy tales, original tales, true narratives, and ghost stories, told at the annual National Storytelling Festival from 1973 to 1990. Includes information about the storytellers, the tales, and the background of the festival.
Includes indexes.
Keywords: Tales; Tales -- United States; Storytelling festivals -- United States; Folklore; Storytelling